Proinflammatory Cytokine Profile is Critical in Autocrine GH-Triggered Curcumin Resistance Engulf by Atiprimod Cotreatment in MCF-7 and MDA-MB-231 Breast Cancer Cells - Çoker-Gürkan, Ajda; Özakaltun, Buse; Akdeniz, Berre-Serra; Ergen, Berfin; YERLİKAYA, PINAR OBAKAN; Akkoç, Tunç; ARISAN, ELİF DAMLA (Springer, 2020)
Active growth hormone (GH) signaling triggers cellular growth and invasion-metastasis in colon, breast, and prostate cancer. Curcumin, an inhibitor of NF-kappa B pathway, is assumed to be a promising anti-carcinogenic agent. Atiprimod is also an anti-inflammatory, anti-carcinogenic agent that induces apoptotic cell death in hepatocellular carcinoma, multiple myeloma, and pituitary adenoma. We aimed to demonstrate the potential additional effect of atiprimod on curcumin-induced apoptotic cell death via cytokine expression profiles in MCF-7 and MDA-MB-231 cells with active GH signaling. The effect of curcumin and/or atiprimod on IL-2, IL-4, and IL-17A levels were measured by ELISA assay. MTT cell viability, trypan blue exclusion, and colony formation assays were performed to determine the effect of combined drug exposure on cell viability, growth, and colony formation, respectively. Alteration of the NF-kappa B signaling pathway protein expression profile was determined following curcumin and/or atiprimod exposure by RT-PCR and immunoblotting. Finally, the effect of curcumin with/without atiprimod treatment on Reactive Oxygen Species (ROS) generation and apoptotic cell death was examined by DCFH-DA and Annexin V/PI FACS flow analysis, respectively. Autocrine GH-mediated IL-6, IL-8, IL-10 expressions were downregulated by curcumin treatment. Atiprimod co-treatment increased the inhibitory effect of curcumin on cell viability, proliferation and also increased the curcumin-triggered ROS generation in each GH(+) breast cancer cells. Combined drug exposure increased apoptotic cell death through acting on IL-2, IL-4, and IL-17A secretion. Forced GH-triggered curcumin resistance might be overwhelmed by atiprimod and curcumin co-treatment via modulating NF-kappa B-mediated inflammatory cytokine expression in MCF-7 and MDA-MB-231 cells.
Keywords: Growth Hormone; Atiprimod; Curcumin; Proinfammatory Cytokine; Apoptosis; Breast Cancer